Stres Akulturatif pada Mahasiswa Internasional di Universitas Airlangga - Indonesia - Shahzad Ali; Nono Hery Yoenanto; Duta Nurdibyanandaru (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
Globalization and the development of modern education systems make foreign students more important in higher education. In Indonesia, in recent years the number of international students has increased. International students, supervisors, and institutions are trying to identify possible ways that can help foreign students adapt to the Indonesian environment, which has its uniqueness. This research aims to investigate the level of acculturative stress experienced by international students of Airlangga University, Indonesia. Specifically, it focused on international students of master programs originating from countries on the African continent. This research was quantitative research. Participants in this research were 40 students. Participants were selected using a purposive sampling technique. The questionnaire was used to collect data and the results were analyzed using SPSS software. Acculturative Stress Scale for International Students (ASSIS) was used to determine the homesickness experienced by the participants. This research found that significant positive acculturative stress among international students (SD=23.87333), (mean=3.00) on homesickness. The result shows that international students experience homesickness because of not having experience living in a different culture and country. The results showed that African students are experiencing high homesickness.